Integrating Irrigation and Potable Water via a Pump-Fed Reservoir: Operational Scenarios and Economic Feasibility in Sukodono - Rahmah Dara Lufira; Suwanto Marsudi; Ussy Andawayanti; M. Amar Sajali; Rizki Tri Utami; Santi Sari; Rizki Ramadani Pratama (Postgraduate, University of Mataram, 2025)
The Sukodono Reservoir (Gresik, East Java, Indonesia) is a pump-fed, multi-compartment system integrating irrigation and potable supply. We assess scenario-based operations and an economic appraisal. Three vertical-turbine pumps are installed (3×150 L/s); routine operation uses two units at 81% efficiency, yielding 243 L/s for 12 h/day (10.498 m³/day), with the third unit as standby/peak. By 2039, the population is projected at 30.801, requiring 22 L/s, supplied by a 30 L/s WTP. Irrigation storage targets are 120.000 m³ (250 ha core plantation), 270.000 m³ (2.250 ha inter-cropping), and 546.750 m³ (secondary crops). Six phased-expansion scenarios over six years were evaluated. Results show the designed operation reliably meets the 22 L/s potable demand while achieving the irrigation storage targets across scenarios. Base-case economics at a 5.50% discount rate (WACC) indicate IRR 18.50%, BCR ≈ 1.00 (break-even), and payback 7.10 years. We conclude that pump-fed reservoirs can integrate rural water supply and dryland irrigation effectively, although economic performance is marginal under the base case; viability improves with efficiency gains and prudent O&M/Fuel-Cost control.